Pengaruh Harga, Kualitas Pelayanan Elektronik, dan Strategi Pemasaran Terhadap Peningkatan Volume Penjulan UMKM "Daster Masakini" di Karanganyar (Studi Kasus Pada Penjualan Daster Pada e-Commerce Shopee - Graha Gustida; Sri Isfantin Puji Lestari; Agus Triatmono (JURNAL WIRANOMIKA, 2025)
This study aims to determine the variables Price (X1), Electronic Service Quality (X2), and Marketing Strategy (X3) that affect the Increase in Sales Volume (Y) of MSME Daster Masakini in Karanganyar. This study uses multiple linear regression analyzed using IBM SPSS 25 software, the regression equation obtained is Y = 0.036 + 0.231 X1 + 0.316 X2 + 0.346 X3 + e. The data used are primary data using the entire population with a total of fifty-two respondents studied in the e-commerce shopee MSME Daster Masakini. The findings show that the Price variable (X1) t count (1.773) t table < (2.011), the hypothesis is rejected which means that there is no significant partial influence on the Increase in Sales Volume (Y) of MSME Daster Masakini in Karanganyar. Electronic Service Quality (X2) tcount (2.911) ttable > (2.011), the hypothesis is accepted which means that there is a significant partial influence on the Increase in Sales Volume (Y) of Daster Masakini UMKM in Karanganyar. Marketing Strategy (X3) tcount (2.793) ttable > (2.011), the hypothesis is accepted which means that there is a significant partial influence on the Increase in Sales Volume (Y) of Daster Masakini UMKM in Karanganyar. The results of the F test show that the F count value (36.770) > F table (3.191), the hypothesis is rejected which means that there is a significant simultaneous influence of the variables Price (X1), Electronic Service Quality (X2), and Marketing Strategy (X3) on the Increase in Sales Volume (Y). Of the four independent variables, the dominant one is Marketing Strategy (X3) where the largest beta value is 0.346, so it can be said that the marketing strategy variable has the most dominant influence on the increase in sales volume of Daster Masakini UMKM in Karanganyar. Keywords: Price (X1), Electronic Service Quality (X2), and Marketing Strategy (X3) and Increasing Sales Volume (Y)